Empathy and Psychosocial Adjustment in Tibetan and Han Adolescents: A Person-Centered Approach - Ma, Chunhua; Ma, Yongfeng; Wang, Youpeng; Lan, Xiaoyu (Frontiers in Psychology, 2019)
Although prior research has shown potential academic difficulties for Tibetan adolescents when coping with the mainstream Han culture, little is known about their psychosocial adjustment. Adopting a person-centered approach, the current study explores psychosocial adjustment profiles based on internalizing indicators (i.e., depression, loneliness, life satisfaction, positive affect, and negative affect) and externalizing indicators (i.e., prosocial behavior and antisocial behavior). Moreover, guided by the empathy theory, this study also examines the direct and interactive effects of empathy (affective and cognitive empathy) and ethnicity on psychosocial adjustment profiles. A total of 306 Tibetan adolescents (66.3% girls) and 321 Han adolescents (55.1% girls) were involved in this study, and participants were asked to fill in a set of self-report questionnaires. A latent profile analysis revealed five psychosocial adjustment profiles: adaptive, maladaptive, externalizing, internalizing, and moderate. Furthermore, a multiple multinomial analysis showed Han adolescents were more likely than Tibetan adolescents to be a member of adaptive and moderate profiles than of the externalizing profile. Individuals with low affective empathy and high cognitive empathy were prone to be adequate in terms of psychosocial functioning, and the effects of low affective empathy and high cognitive empathy on psychosocial functioning were highlighted in Han adolescents only.